Analysis of Choosing A Tools Supplier for Project Procurement Process with Analytical Hierarchy Process (AHP) Method - Rigel Pawallo (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
At the process of procurement construction project, to choose a qualified tools supplier will help the work on project to run without any obstacles and right on schedule. In the choose a tools supplier without any specific policy, will causing the contractor disadvantages in time, cost and quality because the lack of professionality from the supplier. As a solutive act, a contractor must made a choice based on some of positive aspect that owned by the supplier. The purpose of this research is for analize the factors that influenced contractors policies to choose tools supplier and also determine application of the procedure in process of the choice supplier for procurement of tools by online. The analysis starts with validating the variables from literatures in general to some of respondents, and then analysing the result questioners with a method that similar to analytical hierarchy process. With these methods of research, it will show the main factors that influenced contractors for choice of tools supplier. Based on statictical analysis it is known that main factors that influenced the policies for choosing of tools supplier at the process of purchase project are the quality of tools, price of tools, conformity to spesificantions, collateral provided supplier, easiness in payment condition and method, speed and timelines of delivery tools. While for application of grooves according to procedure based on data flow diagram (DFD) that required the application of grooves with supplier choice system on procurement of tools by online.